Émile Durkheim and the birth of the gods : clans, incest, totems, phratries, hordes, mana, taboos, corroborees, sodalities, menstrual blood, apes, churingas, cairns, and other mysterious things /: clans, incest, totems, phratries, hordes, mana, taboos, corroborees, sodalities, menstrual blood, apes, churingas, cairns, and other mysterious things. (2018) - Maryanski, Alexandra
No abstract available